PTFE (Polytetrafluoroethylene) chopped fiber with internal core-shell structure as well as preparation method and application of PTFE chopped fiber

By preparing PTFE short -cut fiber with internal nuclear shell structure, the problem of high -frictional wear rates in PTFE short -cut fibers in the early stages of friction is solved, and low friction and high -powered properties of the friction and wear running stage are realized.

CN119372806AActive Publication Date: 2025-01-28JIHUA LAB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411760298.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing PTFE chopped fibers have a high friction coefficient, large friction torque, and faster heat generation, resulting in a fast wear rate in the early stage and are difficult to apply in fields that limit the starting torque.

Method used

The PTFE short -cut fiber preparation method with an inner nuclear shell structure is adopted. By preparing the PTFE concentration liquid, spinning and sintering treatment with the nuclear shell structure, a PTFE short -cut fiber with an inner nuclear shell structure is formed.

Benefits of technology

This technology enables PTFE short -cut fibers to quickly release PTFE particles below the micrometer below the micrometer, generate a fast motorist lubricating metastasis, reduce friction and wear, and improve the mechanical strength of the self -lubricating composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372806A_ABST
    Figure CN119372806A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid lubrication, and discloses a PTFE chopped fiber with an internal core-shell structure and a preparation method and application thereof.The preparation method of the PTFE chopped fiber with the internal core-shell structure comprises the following steps that 1, a PTFE concentrated solution with the core-shell structure is prepared; (2) preparing a PTFE nascent fiber with an internal core-shell structure; and (3) preparing the PTFE chopped fiber with an internal core-shell structure. The PTFE chopped fiber with the internal core-shell structure has the advantages of being small in size and good in dispersity, the internal core-shell structure of the PTFE chopped fiber with the internal core-shell structure can rapidly release PTFE particles smaller than micrometers along with friction in the friction wear running-in stage, rapid generation of a friction pair lubricating transfer film is facilitated, and the friction pair lubricating transfer film can be rapidly formed. And frictional wear is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solid lubrication technology, and mainly to a PTFE chopped fiber with an intrinsic core-shell structure, a preparation method and an application thereof. Background Art

[0002] In the field of self-lubrication, common products with core-shell structures include organic shell oil-containing microcapsules, inorganic shell silica oil-containing microcapsules, carbon ball oil-containing microcapsules, etc. Although these products can provide good lubricity, after the shell material is destroyed to release the lubricating oil inside, the shell material will form a hollow structure. Even if a small amount of oil-containing microcapsules are added as lubricating materials, the mechanical properties of the composite self-lubricating materials will be greatly reduced.

[0003] In terms of high-load lubricating composite materials, polytetrafluoroethylene (PTFE) particles, PTFE chopped fibers and PTFE compositions are often used as additive components for solid lubrication because of their good lubrication properties. However, when PTFE particles are used as lubricating fillers, the mechanical properties of the matrix are greatly reduced because the PTFE particles themselves are easy to agglomerate and difficult to disperse evenly in the matrix; when PTFE chopped fibers are used as lubricating fillers, the friction coefficient is high in the early stage of friction, the friction torque is large, and the heat generation is fast, resulting in a fast early wear rate, which makes it difficult to use in fields with restrictions on starting torque.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a PTFE chopped fiber with an intrinsic core-shell structure and a preparation method and application, aiming to solve the problems of the existing PTFE chopped fibers.

[0006] The technical solution of this application is as follows: A method for preparing PTFE chopped fibers with an intrinsic core-shell structure, comprising the following steps: (1) Preparation of PTFE concentrate with core-shell structure: diluting the PTFE concentrated dispersion with deionized water to obtain a PTFE dispersion; Under a nitrogen environment, adding methacrylamide to the PTFE dispersion, and then dropping methyl methacrylate, and heating in a water bath to 70-80° C. after the dropping is completed to obtain a first mixed solution; Add potassium persulfate solution dropwise to the first mixed solution, and after the addition is complete, react for at least 8 hours to obtain a reaction solution; The reaction solution is sieved and distilled under reduced pressure to obtain the PTFE concentrated solution with a core-shell structure; (2) Preparation of PTFE primary fibers with intrinsic core-shell structure: Dissolving sodium alginate in water to obtain a sodium alginate carrier solution; The PTFE concentrate with a core-shell structure is added to the sodium alginate carrier solution to obtain a second mixed solution, and an organosilicon defoamer is added dropwise to perform defoaming to obtain a spinning solution; The spinning solution is spun, and CaCl 2 The solution is coagulated in a bath, washed in an ethanol solution, and rolled up to obtain the PTFE primary fiber with an intrinsic core-shell structure; (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure: The PTFE primary fiber with an internal core-shell structure is subjected to a first sintering process at a sintering temperature of 280-325° C. for a sintering time of 5-15 min, and then cut to obtain mm-level chopped fibers; The mm-scale chopped fibers are subjected to a second sintering process at a sintering temperature of 300-325° C. for a sintering time of 20-30 min, and then ground to obtain the PTFE chopped fibers with an intrinsic core-shell structure.

[0007] The method for preparing the PTFE chopped fibers with an internal core-shell structure, wherein, by weight, the amount of the PTFE concentrated dispersion is 50 parts, the amount of the methacrylamide is 20-30 parts, and the amount of the methyl methacrylate is 120-130 parts; The concentration of the PTFE concentrated dispersion is 60wt%.

[0008] The method for preparing the PTFE chopped fibers with an internal core-shell structure, wherein the method for preparing the potassium persulfate solution is to dissolve potassium persulfate in 20 parts of deionized water; The amount of potassium persulfate added is 0.05 g per 100 g of the first mixed solution.

[0009] The method for preparing PTFE chopped fibers with an internal core-shell structure, wherein the process of diluting the PTFE concentrated dispersion with deionized water is to dilute the PTFE concentrated dispersion with 500-700 parts of the deionized water; The reduced pressure distillation is to distill the reaction solution under reduced pressure to 250-350 parts.

[0010] The method for preparing PTFE chopped fibers with an intrinsic core-shell structure, wherein the process of dissolving sodium alginate in water to obtain a sodium alginate carrier solution specifically comprises the following steps: 600 parts of distilled water were placed in a container by mass, stirring was started, and the mixture was heated to 75°C and rotated at 200 RPM. 30 parts of the sodium alginate were weighed and added to the container in batches. After the sodium alginate was completely added, the rotation speed was increased to 400 RPM, and the mixture was stirred for at least 3 hours and degassed to obtain the sodium alginate carrier solution.

[0011] The method for preparing the PTFE chopped fibers with an intrinsic core-shell structure, wherein 400 to 600 parts of the PTFE concentrate with a core-shell structure are added to every 30 parts of the sodium alginate; 0.05 g of organosilicon defoamer was added per 100 g of the second mixed solution.

[0012] The method for preparing the PTFE chopped fibers with an intrinsic core-shell structure, wherein during the spinning process, the spinneret diameter is set to 40-60 μm; The CaCl 2 The mass concentration of the solution is 1-4%, and the mass concentration of the ethanol solution is 50%; In step (3), during the cutting process, the cutting speed is 2 times / s, and the grinding process time is at least 15 minutes; The size of the PTFE chopped fibers with an internal core-shell structure is 50-300 μm.

[0013] A PTFE chopped fiber with an intrinsic core-shell structure, wherein the PTFE chopped fiber with an intrinsic core-shell structure is prepared by the preparation method of the PTFE chopped fiber with an intrinsic core-shell structure as described above.

[0014] An application of the PTFE chopped fibers with an intrinsic core-shell structure as described above, wherein the PTFE chopped fibers with an intrinsic core-shell structure are used to prepare a self-lubricating composite material.

[0015] The application of the PTFE chopped fibers with an intrinsic core-shell structure, wherein the preparation method of the self-lubricating composite material comprises the following steps: The PTFE chopped fibers with an internal core-shell structure are added to a liquid heat-curable resin, and the mixture is fully stirred at room temperature, and then a resin curing component is added, and the stirring is continued to make the system uniform; after vacuum degassing, curing treatment is performed to obtain the self-lubricating composite material; The total amount of the PTFE chopped fibers with an intrinsic core-shell structure and the liquid heat-curable resin is 100% by mass, wherein the PTFE chopped fibers with an intrinsic core-shell structure account for 5-40% and the remainder is the liquid heat-curable resin; The liquid heat-curable resin is a liquid vinyl resin, a liquid epoxy resin or a liquid polyurethane resin.

[0016] Beneficial effects: The PTFE chopped fibers with an intrinsic core-shell structure of the present application have the characteristics of small size and good dispersibility. During the friction and wear running-in stage, as the friction proceeds, the intrinsic core-shell structure of the PTFE chopped fibers with an intrinsic core-shell structure can quickly release PTFE particles below micrometers, which is conducive to the rapid generation of the lubrication transfer film of the friction pair and reduces friction and wear. At the same time, the rod-like structure of the PTFE chopped fibers with an intrinsic core-shell structure has a small effect on the mechanical strength of the self-lubricating composite material compared to the spherical structure of the powder, so the self-lubricating composite material containing the PTFE chopped fibers with an intrinsic core-shell structure has advantages in both mechanical and friction properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscopy result of the PTFE concentrate with a core-shell structure in Example 1 of the present application.

[0018] Figure 2 This is a scanning electron microscope result of the PTFE chopped fibers with an intrinsic core-shell structure in Example 1 of the present application.

[0019] Figure 3 This is a graph showing the test results of the coefficient of friction in Example 1 of the present application.

[0020] Figure 4 This is a graph of the compression strength test and wear rate measurement results in Example 1 of the present application. DETAILED DESCRIPTION

[0021] The present application provides a PTFE chopped fiber with an internal core-shell structure, a preparation method and an application. In order to make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0022] The present application provides a method for preparing PTFE chopped fibers with an intrinsic core-shell structure, comprising the following steps: (1) Preparation of PTFE concentrate with core-shell structure: Dilute the PTFE concentrated dispersion with deionized water (DI water) to obtain a diluted PTFE dispersion: according to the mass fractions, take 50 parts of 60wt% PTFE concentrated dispersion and 500-700 parts of deionized water (DI water), add them into a four-necked flask in sequence, start stirring at room temperature, stir evenly at 400-600RPM, and obtain a diluted PTFE dispersion; 20-30 parts of methacrylamide (MAM) are added to a four-necked flask filled with nitrogen, and then 120-130 parts of methyl methacrylate (MMA) are slowly added dropwise to the four-necked flask. After the addition is completed, a water bath is turned on to heat to 70-80° C. to obtain a first mixed solution; Take an appropriate amount of potassium persulfate (0.05 g per 100 g of the first mixed solution) and dissolve it in 20 parts of DI water to obtain a potassium persulfate solution, and slowly add the potassium persulfate solution dropwise to the first mixed solution. After the addition is completed, react for at least 8 hours to obtain a reaction solution; The reaction solution was filtered with a 50-mesh screen to remove a small amount of agglomerated precipitated material, and then placed in a rotary evaporator for reduced pressure distillation to 250-350 parts to obtain a PTFE concentrate with a core-shell structure ((MMA-MAM)@PTFE) that can be used for carrier spinning.

[0023] In the present application, MAM and MMA are used as shell reaction monomers of the (MMA-MAM)@PTFE) core-shell structure, and free radical polymerization occurs on the surface of PTFE particles to form a core-shell structure of (MMA-MAM) coated PTFE. The introduction of MAM can improve the thermal stability of the MAM-MMA copolymer, so that the shell material has both high heat resistance and good thermal stability, which can prevent the core-shell structure from being destroyed by heat during the subsequent sintering process. When the MAM / MMA ratio is 20:130~30:120, its heat resistance is the best.

[0024] In this step, after the reaction solution is prepared, it is distilled under reduced pressure to 250-350 parts, so as to increase the content of the PTFE concentrate having a core-shell structure in the spinning solution.

[0025] (2) Preparation of PTFE primary fibers with intrinsic core-shell structure: Dissolve sodium alginate in water to obtain a sodium alginate carrier solution: according to the mass fraction, take 600 parts of distilled water and put them into a three-necked flask, start stirring, heat to 75°C, rotate at 200 RPM, weigh 30 parts of sodium alginate and add them into the three-necked flask in batches, after complete addition, increase the rotation speed to 400 RPM, stir for at least 3 hours, and degas to obtain a sodium alginate carrier solution; 400-600 parts of the PTFE concentrate with a core-shell structure are added to the sodium alginate carrier solution to obtain a second mixed solution, a small amount of an organosilicon defoamer is added dropwise (0.05 g is added dropwise per 100 g of the second mixed solution), and the mixture is stirred for at least 8 hours and degassed to obtain a spinning solution; Pour the spinning solution into the spinning machine solution tank, turn on the metering pump, the spinneret diameter is 40-60 μm, and manually pull through the CaCl 2The solution was placed in a coagulation bath, washed with an ethanol solution having a mass concentration of 50%, and rolled up to obtain PTFE primary fibers with an intrinsic core-shell structure.

[0026] In the present application, the spinneret diameter is set to 40-60 μm. If it is lower than 40 μm, the wire will break easily during the wire drawing process. If it is higher than 60 μm, the mechanical properties of the product will decrease.

[0027] (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure: The PTFE primary fiber with an intrinsic core-shell structure is sintered in a muffle furnace at 280-325°C for 5-15 minutes to obtain a light brown fiber, which is then cut using a fiber cutting machine with a feed speed of 5-10 mm / min and a cutter speed of 2 times / s to obtain mm-level chopped fibers; The mm-sized chopped fibers were sintered at 300-325°C for 20-30 min in a muffle furnace to obtain light brown chopped fibers, which were then ground using a fiber crusher for at least 15 min to obtain PTFE chopped fibers with an intrinsic core-shell structure having a size of 50-300 μm.

[0028] In the present application, the first short-time sintering can obtain fibers with insufficient carrier sintering, at which point the fibers have poor toughness and are easy to cut, making them suitable for cutting. The second sintering can obtain fibers with sufficient carrier sintering, increase the PTFE content in the fibers, and thus improve the self-lubricating properties of the fibers. This solution first cuts to mm, which is beneficial for subsequent grinding to achieve the desired size and uniformity.

[0029] The present application also provides a PTFE chopped fiber with an intrinsic core-shell structure, which is prepared by using the above-mentioned method for preparing the PTFE chopped fiber with an intrinsic core-shell structure.

[0030] The PTFE chopped fibers with an intrinsic core-shell structure of the present application have the characteristics of small size and good dispersibility. During the friction and wear running-in stage, as the friction proceeds, the intrinsic core-shell structure of the PTFE chopped fibers with an intrinsic core-shell structure can quickly release PTFE particles below micrometers, which is conducive to the rapid generation of a lubricating transfer film for the friction pair and reduces friction and wear. At the same time, the rod-like structure of the PTFE chopped fibers with an intrinsic core-shell structure has a small effect on the mechanical strength of the self-lubricating composite material compared to the spherical structure of the powder, so the self-lubricating composite material containing the PTFE chopped fibers with an intrinsic core-shell structure has advantages in both mechanical and friction properties.

[0031] The present application also provides an application of PTFE chopped fibers with an intrinsic core-shell structure, and the PTFE chopped fibers with an intrinsic core-shell structure are used to prepare a self-lubricating composite material.

[0032] Furthermore, the preparation method of the self-lubricating composite material comprises the following steps: The PTFE chopped fibers with an intrinsic core-shell structure are added to a liquid heat-curable resin at a certain mass fraction, fully stirred and mixed at room temperature, and then the resin curing component is added, and stirring is continued to make the system uniform; vacuum degassing is performed and curing treatment is performed to obtain a self-lubricating composite material containing the PTFE chopped fibers with an intrinsic core-shell structure.

[0033] Calculated by mass fraction, the total amount of PTFE chopped fibers with an intrinsic core-shell structure and liquid heat-curable resin is 100%, of which PTFE chopped fibers with an intrinsic core-shell structure account for 5-40% and the remainder is the liquid heat-curable resin.

[0034] Furthermore, the liquid heat-curable resin may be a liquid vinyl resin, a liquid epoxy resin, a liquid polyurethane resin, or the like.

[0035] The dispersibility of lubricating fillers can generally be judged by observing the dispersion of lubricating fillers in the resin after adding the lubricating fillers to the resin matrix. For example, PTFE powder (McLean) often presents lumps of more than mm in the resin matrix. However, after the PTFE chopped fibers with an intrinsic core-shell structure of the present application are added to the resin matrix, the PTFE chopped fibers with an intrinsic core-shell structure of the present application do not agglomerate themselves and are evenly dispersed in the resin matrix, and have good dispersibility.

[0036] The self-lubricating composite material containing the PTFE chopped fibers with an inherent core-shell structure of the present application achieves low friction, short running-in time, stable friction coefficient, and low wear over a long period of time, and can be applied to aerospace, heavy machinery and other fields. In the embodiment of the present application, the self-lubricating composite material containing the PTFE chopped fibers with an inherent core-shell structure of the present application has a bearing strength of 95 MPa, a friction coefficient of 0.11, and a wear rate of 6.7*10 -6 mm 3 / Nm, it is a good high-load self-lubricating material.

[0037] The present application is further described below through specific embodiments.

[0038] Example 1 (1) Preparation of PTFE concentrate with core-shell structure, the specific operation is as follows: 1. Take 50 g of 60wt% PTFE concentrated dispersion (McLean reagent) and 600 g of DI water, add them into a four-necked flask in sequence, start stirring at 500 RPM at room temperature, and stir thoroughly for 30 minutes to obtain a diluted PTFE dispersion.

[0039] 2. Take 20 g of methacrylamide (MAM) and add it to a four-necked flask filled with nitrogen. Then take 130 g of methyl methacrylate (MMA) and slowly add it dropwise to the four-necked flask. After the addition is completed, turn on the water bath to heat to 75°C.

[0040] 3. Take 0.4g potassium persulfate and dissolve it in 20g DI water, and slowly add it dropwise to the mixed solution prepared in step 2. After the addition is completed, ensure the reaction for 8 hours.

[0041] 4. The reaction solution prepared in step 3 was filtered through a 50-mesh screen to remove a small amount of agglomerated precipitated material, and then subjected to reduced pressure distillation on a rotary evaporator to 300 g to obtain a PTFE concentrate with a core-shell structure (MMA-MAM)@PTFE) that can be used for carrier spinning.

[0042] (2) Preparation of PTFE primary fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. Take 600 g of distilled water and place it in a three-necked flask. Start stirring and heat to 75°C at a speed of 200 RPM. Weigh 30 g of sodium alginate and add it to the three-necked flask in small batches. After it is completely added, increase the speed to 400 RPM, stir for 3 h, and degas to obtain a sodium alginate carrier solution.

[0043] 2. Add 400 g of PTFE concentrate with a core-shell structure to the above-mentioned sodium alginate carrier solution, drop 0.5 g of silicone defoamer, stir thoroughly for 8 h, degas, and obtain a spinning solution.

[0044] 3. Pour the above spinning solution into the spinning machine solution tank, turn on the metering pump, the spinneret diameter is 40 μm, and manually pull through the CaCl 2 The solution was placed in a coagulation bath, then washed with an ethanol solution having a mass concentration of 50%, and rolled up to obtain PTFE primary fibers with an intrinsic core-shell structure.

[0045] (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. The PTFE primary fiber with an intrinsic core-shell structure was sintered at 300°C in a muffle furnace for 10 minutes to obtain light brown fibers, which were then cut using a fiber cutting machine with a feed rate of 5 mm / min and a cutter speed of 2 times / s to obtain mm-level chopped fibers; 2. The mm-grade chopped fibers were sintered at 300° C. for 30 minutes in a muffle furnace to obtain light brown chopped fibers, which were then ground using a fiber crusher for 15 minutes to obtain PTFE chopped fibers with an intrinsic core-shell structure.

[0046] (4) Preparing a vinyl resin composite material containing PTFE chopped fibers with an intrinsic core-shell structure, the specific operation is as follows: According to the mass fraction, 30% of PTFE chopped fibers with an intrinsic core-shell structure were added to 70% of liquid vinyl resin (901 vinyl resin), and the mixture was fully stirred at room temperature. Then, 0.5% of dibenzoyl peroxide (BPO) and 0.5% of cobalt cyclohexaneate were added to the liquid vinyl resin, and the mixture was stirred to make the system uniform. After vacuum degassing, the mixture was heated from room temperature to 60°C at 1°C / min and kept warm for 6 h for curing to obtain a vinyl resin composite material containing PTFE chopped fibers with an intrinsic core-shell structure.

[0047] The PTFE concentrate with core-shell structure in this example was tested using a scanning electron microscope. The results are shown in Figure 1 The structure of the core-shell PTFE is spherical and its size is between 300 and 500 nm.

[0048] The PTFE chopped fibers with an intrinsic core-shell structure in this embodiment were tested using a scanning electron microscope. The results are shown in Figure 2 The fiber diameter of the PTFE chopped fiber with an intrinsic core-shell structure is about 50 μm, the length is about 100 μm, and the core-shell structure components can be seen inside the fiber.

[0049] The compression strength test, friction coefficient test and wear rate measurement were carried out using a universal testing machine, a Bruker UMT friction and wear tester and a Bruker white light interferometer, respectively.

[0050] Test conditions: The universal testing machine test condition is 1mm / min loading speed; the Bruker UMT friction and wear tester uses a reciprocating drive module, with a loading force of 20 N, a frequency of 5HZ, a stroke of 3mm, and a grinding pattern of a 10mm diameter steel ball; the Bruker white light interferometer analyzes the wear rate of the wear scar after the UMT test.

[0051] The vinyl resin composite material containing 30%wt of PTFE chopped fibers with an internal core-shell structure prepared in this embodiment was used as the test object, and the comparative samples were pure vinyl resin (901 resin), a vinyl resin composite material containing 30%wt of PTFE powder (McLean), and a vinyl resin composite material containing 30%wt of PTFE chopped fibers (Toray Teflon™ PTFE Fibers). The comparative samples and the vinyl resin composite material containing 30%wt of PTFE chopped fibers with an internal core-shell structure in this embodiment were prepared in the same manner, with the only difference being the different lubricating fillers used.

[0052] Among them, when preparing a vinyl resin composite material containing 30%wt PTFE powder (McLean), the dispersion of PTFE powder in liquid vinyl resin was observed after the PTFE powder was added to the vinyl resin, and the PTFE powder showed lumps of more than mm in the liquid vinyl resin; when the PTFE chopped fibers with an intrinsic core-shell structure of this embodiment were added to the liquid vinyl resin, the PTFE chopped fibers with an intrinsic core-shell structure did not agglomerate themselves and were evenly dispersed in the liquid vinyl resin, proving that the PTFE chopped fibers with an intrinsic core-shell structure of this embodiment have good dispersibility.

[0053] (1) Friction coefficient test results Test results such as Figure 3 As shown in the COF test results, as the friction and wear progresses, the vinyl resin composite material containing 30%wt of PTFE chopped fibers with an internal core-shell structure (corresponding to Figure 3 The COF of the “PTFE chopped fiber composite resin with an intrinsic core-shell structure” in the above formula decreases rapidly and stabilizes at around 0.11. The vinyl resin composite material containing 30%wt PTFE chopped fibers (corresponding to Figure 3 The initial COF of the "PTFE chopped fiber composite resin" in the above formula is relatively high, and stabilizes at around 0.12 with continuous friction. The vinyl resin composite material containing 30%wt PTFE powder (McLean) (corresponding to Figure 3 The initial COF of the "PTFE powder composite resin" is low, but the COF coefficient is unstable, which is related to its uneven distribution.

[0054] (2) Compression strength test and wear rate measurement results like Figure 4 As shown in the mechanical test results, the vinyl resin composite material containing 30%wt PTFE powder (McLean) (corresponding to Figure 4 The "PTFE powder composite resin" in the above formula has the lowest strength. PTFE powder will cause the bearing strength of vinyl resin to drop significantly. The vinyl resin composite material containing 30%wt of PTFE chopped fibers with an internal core-shell structure (corresponding to Figure 4 The "PTFE chopped fiber composite resin with an internal core-shell structure" and the vinyl resin composite material containing 30%wt PTFE chopped fibers (corresponding to Figure 4 The wear rate measurement results show that the vinyl resin composite material containing 30%wt of PTFE chopped fibers with an intrinsic core-shell structure (corresponding to Figure 4 The wear rate of the composite resin with PTFE chopped fibers having an internal core-shell structure is the lowest, and the vinyl resin composite material containing 30%wt PTFE powder (McLean) (corresponding to Figure 4 The wear rate of "PTFE powder composite resin" is the highest.

[0055] In summary, the vinyl resin composite material containing 30%wt of PTFE chopped fibers with an intrinsic core-shell structure prepared in Example 1 has a bearing strength of 95 MPa, a friction coefficient of 0.11, and a wear rate of 6.7*10 -6 mm 3 / Nm, with good mechanical and tribological properties.

[0056] Example 2 (1) Preparation of PTFE concentrate with core-shell structure, the specific operation is as follows: 1. Take 50 g of 60wt% PTFE concentrated dispersion (McLean reagent) and 600 g of DI water, add them into a four-necked flask in sequence, start stirring at 500 RPM at room temperature, and stir thoroughly for 30 minutes to obtain a diluted PTFE dispersion.

[0057] 2. Take 30 g of methacrylamide (MAM) and add it to a four-necked flask filled with nitrogen. Then take 120 g of methyl methacrylate (MMA) and slowly add it dropwise to the four-necked flask. After the addition is completed, turn on the water bath to heat to 75°C.

[0058] 3. Take 0.4g potassium persulfate and dissolve it in 20g DI water, and slowly add it dropwise to the mixed solution prepared in step 2. After the addition is completed, ensure the reaction for 8 hours.

[0059] 4. The reaction solution prepared in step 3 above was filtered through a 50-mesh screen to remove a small amount of agglomerated precipitated material, and then subjected to reduced pressure distillation on a rotary evaporator to 300 g to obtain a PTFE concentrate with a core-shell structure (MMA-MAM)@PTFE) that can be used for carrier spinning.

[0060] (2) Preparation of PTFE primary fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. Take 600 g of distilled water and place it in a three-necked flask. Start stirring and heat to 75°C at a speed of 200 RPM. Weigh 30 g of sodium alginate and add it to the three-necked flask in small batches. After it is completely added, increase the speed to 400 RPM, stir for 3 h, and degas to obtain a sodium alginate carrier solution.

[0061] 2. Add 600 g of PTFE concentrate with a core-shell structure to the above-mentioned sodium alginate carrier solution, add 0.6 g of silicone defoamer, stir well for 8 h, degas, and obtain a spinning solution.

[0062] 3. Pour the above spinning solution into the spinning machine solution tank, turn on the metering pump, the spinneret diameter is 60 μm, and manually pull through the mass concentration of 4% CaCl 2 The solution was coagulated in a bath, washed with a 50% ethanol solution, and rolled up to obtain PTFE primary fibers with an internal core-shell structure.

[0063] (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. The PTFE primary fiber with an intrinsic core-shell structure was sintered at 280 °C in a muffle furnace for 10 minutes to obtain light brown fibers, which were then cut using a fiber cutting machine with a feed rate of 10 mm / min and a cutter speed of 2 times / s to obtain mm-level chopped fibers.

[0064] 2. The mm-grade chopped fibers were sintered at 310° C. for 30 minutes in a muffle furnace to obtain light brown chopped fibers, which were then ground using a fiber grinder for 15 minutes to obtain PTFE chopped fibers with an intrinsic core-shell structure.

[0065] (4) Epoxy resin composite material containing PTFE chopped fibers with an internal core-shell structure, the specific operation is as follows: According to the mass fraction, 35% of PTFE chopped fibers with an intrinsic core-shell structure were added to 65% of liquid epoxy resin (E51 epoxy resin), and the mixture was fully stirred at room temperature. Then, the resin curing agent (isophorone diamine IPDA) was added at a mass ratio of liquid epoxy resin: curing agent = 5:1, and the system was stirred to make it uniform. After vacuum degassing, the mixture was heated from room temperature to 80°C at 1°C / min and kept warm for 6 h for curing to obtain an epoxy resin composite material containing PTFE chopped fibers with an intrinsic core-shell structure.

[0066] The epoxy resin composite material containing PTFE chopped fibers with an internal core-shell structure prepared in Example 2 has a bearing strength of 78 MPa, a friction coefficient of 0.103, and a wear rate of 5.9*10 -6 mm 3 / Nm, with good mechanical and tribological properties.

[0067] Example 3 (1) Preparation of PTFE concentrate with core-shell structure, the specific operation is as follows: 1. Take 50 g of 60wt% PTFE concentrated dispersion (McLean reagent) and 600 g of DI water, add them into a four-necked flask in sequence, start stirring at 500 RPM at room temperature, and stir thoroughly for 30 minutes to obtain a diluted PTFE dispersion.

[0068] 2. Take 30g of methacrylamide (MAM) and add it to a four-necked flask filled with nitrogen. Then take 120g of methyl methacrylate (MMA) and slowly add it dropwise to the four-necked flask. After the addition is completed, turn on the water bath to heat to 75°C.

[0069] 3. Take 0.4 g potassium persulfate and dissolve it in 20 g DI water, and slowly add it dropwise to the mixed solution prepared in step 2. After the addition is completed, ensure the reaction for 8 h.

[0070] 4. The reaction solution prepared in step 3 above was filtered through a 50-mesh screen to remove a small amount of agglomerated precipitated material, and then subjected to reduced pressure distillation on a rotary evaporator to 300 g to obtain a PTFE concentrate with a core-shell structure (MMA-MAM)@PTFE) that can be used for carrier spinning.

[0071] (2) Preparation of PTFE primary fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. Take 600 g of distilled water and place it in a three-necked flask. Start stirring and heat to 75°C at a speed of 200 RPM. Weigh 30 g of sodium alginate and add it to the three-necked flask in small batches. After it is completely added, increase the speed to 400 RPM, stir for 3 h, and degas to obtain a sodium alginate carrier solution.

[0072] 2. Add 550 g of PTFE concentrate with a core-shell structure to the above-mentioned sodium alginate carrier solution, drop 0.55 g of silicone defoamer, stir thoroughly for 8 h, degas, and obtain a spinning solution.

[0073] 3. Pour the above spinning solution into the spinning machine solution tank, turn on the metering pump, the spinneret diameter is 60 μm, and manually pull through 3% mass concentration of CaCl 2 The solution was coagulated in a bath, washed with an ethanol solution having a mass concentration of 50%, and rolled up to obtain PTFE primary fibers with an internal core-shell structure.

[0074] (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure, the specific operation is as follows: 1. The PTFE primary fiber with an intrinsic core-shell structure was sintered at 325°C in a muffle furnace for 10 minutes to obtain light brown fibers, which were then cut using a fiber cutting machine with a feed rate of 10 mm / min and a cutter speed of 2 times / s to obtain mm-level chopped fibers.

[0075] 2. The mm-grade chopped fibers were sintered at 325°C for 30 minutes in a muffle furnace to obtain light brown chopped fibers, which were then ground using a fiber grinder for 15 minutes to obtain PTFE chopped fibers with an intrinsic core-shell structure.

[0076] (4) Preparing a polyurethane resin composite material containing PTFE chopped fibers with an intrinsic core-shell structure, the specific operation is as follows: According to the mass fraction, 35% of PTFE chopped fibers with an intrinsic core-shell structure were added to 65% of liquid polyurethane resin component A (liquid MDI), and the mixture was fully stirred at room temperature. Then, the polyurethane component B containing a resin catalyst (polyether polyol PPG-400 containing 0.2% dibutyltin dilaurate) was added according to the mass ratio of component A: component B = 55:45, and the system was stirred continuously to make it uniform. After vacuum degassing, the mixture was heated from room temperature to 65°C at 1°C / min and kept warm for 6 h for curing to obtain a polyurethane resin composite material containing PTFE chopped fibers with an intrinsic core-shell structure.

[0077] The polyurethane resin composite material containing PTFE chopped fibers with an internal core-shell structure prepared in Example 3 has a bearing strength of 63 MPa, a friction coefficient of 0.87, and a wear rate of 4.8*10 -6 mm 3 / Nm, with good mechanical and tribological properties.

[0078] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing PTFE chopped fibers with an intrinsic core-shell structure, characterized in that: The following steps are involved: (1) Preparation of PTFE concentrate with core-shell structure: diluting the PTFE concentrated dispersion with deionized water to obtain a PTFE dispersion; Under a nitrogen environment, adding methacrylamide to the PTFE dispersion, and then dropping methyl methacrylate, and heating in a water bath to 70-80° C. after the dropping is completed to obtain a first mixed solution; Add potassium persulfate solution dropwise to the first mixed solution, and after the addition is complete, react for at least 8 hours to obtain a reaction solution; The reaction solution is sieved and distilled under reduced pressure to obtain the PTFE concentrated solution with a core-shell structure; (2) Preparation of PTFE primary fibers with intrinsic core-shell structure: Dissolving sodium alginate in water to obtain a sodium alginate carrier solution; The PTFE concentrate with a core-shell structure is added to the sodium alginate carrier solution to obtain a second mixed solution, and an organosilicon defoamer is added dropwise to perform defoaming to obtain a spinning solution; The spinning solution is spun, passed through a coagulation bath of a CaCl2 solution, washed with an ethanol solution, and rolled up to obtain the PTFE primary fiber with an intrinsic core-shell structure; (3) Preparation of PTFE chopped fibers with an intrinsic core-shell structure: The PTFE primary fiber with an internal core-shell structure is subjected to a first sintering process at a sintering temperature of 280-325° C. for a sintering time of 5-15 min, and then cut to obtain mm-level chopped fibers; The mm-scale chopped fibers are subjected to a second sintering process at a sintering temperature of 300-325° C. for a sintering time of 20-30 min, and then ground to obtain the PTFE chopped fibers with an intrinsic core-shell structure.

2. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 1, characterized in that: By weight, the amount of the PTFE concentrated dispersion is 50 parts, the amount of the methacrylamide is 20-30 parts, and the amount of the methyl methacrylate is 120-130 parts; The concentration of the PTFE concentrated dispersion is 60wt%.

3. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 2, characterized in that: The potassium persulfate solution is prepared by dissolving potassium persulfate in 20 parts of deionized water; The amount of potassium persulfate added is 0.05 g per 100 g of the first mixed solution.

4. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 3, characterized in that: The process of diluting the PTFE concentrated dispersion with deionized water is to dilute the PTFE concentrated dispersion with 500-700 parts of the deionized water; The reduced pressure distillation is to distill the reaction solution under reduced pressure to 250-350 parts.

5. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 4, characterized in that: The process of dissolving sodium alginate in water to obtain a sodium alginate carrier solution specifically comprises the following steps: 600 parts of distilled water were placed in a container by weight, stirring was started, and the mixture was heated to 75°C at a speed of 200 RPM. 30 parts of the sodium alginate were weighed and added to the container in batches. After the sodium alginate was completely added, the speed was increased to 400 RPM, and the mixture was stirred for at least 3 hours and degassed to obtain the sodium alginate carrier solution.

6. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 5, characterized in that: For every 30 parts of the sodium alginate, 400-600 parts of the PTFE concentrate with a core-shell structure are added; 0.05 g of organosilicon defoamer was added per 100 g of the second mixed solution.

7. The method for preparing PTFE chopped fibers with an intrinsic core-shell structure according to claim 1, characterized in that: During the spinning process, the spinneret diameter is set to 40-60 μm; The mass concentration of the CaCl2 solution is 1-4%, and the mass concentration of the ethanol solution is 50%; In step (3), during the cutting process, the cutting speed is 2 times / s, and the grinding process time is at least 15 minutes; The size of the PTFE chopped fibers with an internal core-shell structure is 50-300 μm.

8. A PTFE chopped fiber with an intrinsic core-shell structure, characterized in that: The PTFE chopped fibers with an intrinsic core-shell structure are prepared by the method for preparing PTFE chopped fibers with an intrinsic core-shell structure as described in any one of claims 1 to 7.

9. An application of the PTFE chopped fibers with an intrinsic core-shell structure as claimed in claim 8, characterized in that: The PTFE chopped fibers with an intrinsic core-shell structure are used to prepare a self-lubricating composite material.

10. The use of the PTFE chopped fibers with an intrinsic core-shell structure according to claim 9, characterized in that: The preparation method of the self-lubricating composite material comprises the following steps: The PTFE chopped fibers with an internal core-shell structure are added to a liquid heat-curable resin, and the mixture is fully stirred at room temperature, and then a resin curing component is added, and the stirring is continued to make the system uniform; after vacuum degassing, curing treatment is performed to obtain the self-lubricating composite material; The total amount of the PTFE chopped fibers with an intrinsic core-shell structure and the liquid heat-curable resin is 100% by mass, wherein the PTFE chopped fibers with an intrinsic core-shell structure account for 5-40% and the remainder is the liquid heat-curable resin; The liquid heat-curable resin is a liquid vinyl resin, a liquid epoxy resin or a liquid polyurethane resin.

Citation Information

Patent Citations

  • Polytetrafluoroethylene-based core-shell nano composite material as well as preparation method and application thereof

    CN111286047A

  • Preparation method of in-situ reinforced PTFE (Polytetrafluoroethylene) fiber and multi-scale reinforced self-lubricating fabric liner

    CN117661137A

  • Dispersion spinning core-shell fluoropolymers

    US20050143494A1